2009
DOI: 10.1586/ern.09.31
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of a staging model for bipolar disorders

Abstract: A model of staging in the field of bipolar disorder (BD) should offer a means for clinicians to predict response to treatment and more general outcome measures, such as the level of functioning and autonomy. The present staging model emphasizes the assessment of patients in the interepisodic period and includes: latent phase: individuals who present mood and anxiety symptoms and increased risk for developing threshold BD; Stage I--patients with BD who present well established periods of euthymia and absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
205
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 221 publications
(220 citation statements)
references
References 94 publications
9
205
2
4
Order By: Relevance
“…11,12 They converge insofar as all describe a prodromal phase (i.e., stage 0, 11 latent stage 12 ), followed by onset, recurrence, and, finally, chronicity, defining the later stages of the disease as more recurrent, treatmentresistant 11 and socially dysfunctional. 12 While these staging models for BD have been considered theoretically, they must be validated and improved for clinical implementation. A study by Berk et al pooled 12 BD studies and identified that those patients at the earliest stages of the illness had a more favorable response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 They converge insofar as all describe a prodromal phase (i.e., stage 0, 11 latent stage 12 ), followed by onset, recurrence, and, finally, chronicity, defining the later stages of the disease as more recurrent, treatmentresistant 11 and socially dysfunctional. 12 While these staging models for BD have been considered theoretically, they must be validated and improved for clinical implementation. A study by Berk et al pooled 12 BD studies and identified that those patients at the earliest stages of the illness had a more favorable response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nonresponse in bipolar depression, for instance, occurs in 40% of patients [4]. In view of that, bipolar disorder has been conceived in terms of differential stages by some researchers in order to tailor treatments according to patients' needs [5,6]. Staging models imply that natural history of bipolar disorder moves through a predictable temporal progression, and provision of stage-appropriate treatment can modify this course.…”
Section: Introductionmentioning
confidence: 99%
“…In this same vein, Kapczinski and colleagues reported a model that emphasizes the assessment of patients in the inter-episodic period: latent phase -subjects who present family history and anxiety and/or mood symptoms; stage I -bipolar disorder patients who present well-established periods of euthymia and absence of overt psychiatric morbidity between episodes; stage II -patients who present symptoms in between episodes, mostly due to axis I or II comorbidities; stage III -patients who present a clinically relevant pattern of neurocognitive and functioning impairment; and stage IV -patients who are unable to live autonomously due to functional impairment related to bipolar disorder [5]. Authors also suggested that patients at late stages are more likely to present altered brain scans and biomarkers [5]. The progression across these presentations could be determined by the cumulative exposure to mood episodes, trauma, drug abuse, and inherited vulnerability [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations